2011
DOI: 10.4061/2011/926383
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of P(VdF-HFP)-CeO2-LiClO4-Based Composite Microporous Membrane Electrolytes for Li-Ion Batteries

Abstract: Composite microporous membranes based on Poly (vinylidene fluoride-co-hexafluoro propylene) P(VdF-co-HFP)-CeO 2 were prepared by phase inversion and preferential polymer dissolution process. It was then immersed in 1M LiClO 4 -EC/DMC (v/v = 1 : 1) electrolyte solution to obtain their corresponding composite microporous membrane electrolytes. For comparison, composite membrane electrolytes were also prepared by conventional phase inversion method. The surface morphology of composite membranes obtained by both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The addition of CeO 2 NPs to the GPE reduced the interfacial resistance and enabled a wider electrochemical window and good cycling performance. Vijayakumar et al [ 125 ] reported similar results in which the incorporation of CeO 2 reduced the ion coupling and increased the charge carrier number, thereby improving the ionic conductivity. However, an excess of CeO 2 led to an increased dilution effect, which resulted in a continuous decrease in the electrolytic conductance.…”
Section: Details Of the Inorganic Fillers Applied In Gpesmentioning
confidence: 89%
“…The addition of CeO 2 NPs to the GPE reduced the interfacial resistance and enabled a wider electrochemical window and good cycling performance. Vijayakumar et al [ 125 ] reported similar results in which the incorporation of CeO 2 reduced the ion coupling and increased the charge carrier number, thereby improving the ionic conductivity. However, an excess of CeO 2 led to an increased dilution effect, which resulted in a continuous decrease in the electrolytic conductance.…”
Section: Details Of the Inorganic Fillers Applied In Gpesmentioning
confidence: 89%
“…Accordingly to the free volume model, the activation energy should be related to the mobility of the charge carriers [27]. provides a higher free volume on increasing the temperature effect [17]. The thin film electrolyte conductivity behavior is closely resembled to liquid state electrolyte [28].…”
Section: Temperature Dependence Conductivitymentioning
confidence: 99%
“…This is due to the interaction of zinc oxide nanoparticles with PVdF-co-HFP and also due to compatibility. Further addition of filler content into the PVdF-co-HFP polymer matrix increased the crystallinity (29.47%) and also the heat of fusion (28.14) to some extent (Table . 1), due to the steric hindrance of the agglomerated nanoparticles on the polymer matrix [17]. Further, Low crystalline may be originated from the usage of NMP as a solvent, which interacted with VdF chain specifically the interaction between N-atom of NMP and VdF chain and consequently inhibit chain rearrangement.…”
Section: Differential Scanning Calorimetry (Dsc) Analysismentioning
confidence: 99%
See 2 more Smart Citations